Estudo de um programa de MCC em máquina de refrigeração CHILLER - Pansardi, Anderson Tadeu (2012)
This project presents the process of implementation of Reliability Centered Maintenance (RCM) in refrigeration equipment called chiller. This equipment is responsible for refrigeration and water circulation in several machines of the company, what this study is about. The machines where the water circuit is connected are located in lines of spot welding (or soldering strength) that can not overheat. There is also the risk of security breaches due to some resistance welding inverters overheat and explode causing internal capacitors breaks electronics and mechanical components on the machine and possible accidents involving operators who are close to her. Other risks relate to the loss of earnings of the company, once a stop for any failure can lead chiller stops across the weld line, which is responsible for prefabrication of some important products of the company. The purpose of this paper is to consider the losses that the equipment may cause the time it gets stopped due to a fault and unwanted application of MCC in order to make the cooling process more stable. The methodology of this study will be the use of MCC in the refrigeration process taking into consideration the stages studied in the course of Reliability Engineering Applied Maintenance. This monograph it is a proposal of application of MCC and reliability analysis tool has not been developed because of the need approval from management.